Multimedia Quality as Perceived by the User - Monfort, Jean-Yves; Adler, Klemens P. F.; Gierlich, Hans-Wilhelm; Pomy, Joachim (Communications - Scientific letters of the University of Zilina, 2008)
End-to-end voice quality as perceived by the user has always been of major concern to ETSI, the European Telecommunications Standards Institute and its Technical Committee STQ (Speech processing, Transmission and Quality aspects). Recent developments in telecommunications increasingly promote the introduction of new services, including wideband speech communication and multimedia. At the same advent the global telecommunication landscape is undergoing dramatic changes, such as the migration from traditional public network operators to internet (or NGN) service providers. This paper provides an insight into ETSI’s activities for end-to-end multimedia quality for NGN - which is a promotional factor for the market. In a multi-vendor environment with quality not being regulated, standards are the only means to achieve reasonable end-to-end multimedia quality. There will be a huge demand for wideband speech communication and multimedia in hands-free, mobile, nomadic and video phone applications in the near future. Devices designed for such applications will have to rely on non-linear and time variant signal processing in order to be capable of providing speech quality that satisfies users’ demands. Therefore, it is essential to develop state-of-the-art requirements and test methodologies and to standardize them.